Detection of Mumps Virus RNA by Real-Time One-Step Reverse Transcriptase PCR Using the LightCycler Platform - Leblanc, Jason J. (American Society for Microbiology (ASM), 2008)
A real-time reverse transcriptase PCR (RT-PCR) assay that targeted both the mumps virus F gene and human RNase P in clinical samples was adapted for use with the LightCycler platform. LightCycler RT-PCR is as sensitive as conventional nested RT-PCR and significantly less expensive and labor-intensive, making it ideal for mumps diagnosis during outbreaks.